Digital Preservation of Traditional Games: The Role of Community Pioneers in Yogyakarta - Sugiyanti, Umi; Pambudi, Agung (Brawijaya University Library, 2025)
Traditional games are an essential part of Indonesia's cultural heritage, yet they are gradually being replaced by digital entertainment, leading to concerns about their preservation. This study explores the role of community pioneers in Yogyakarta in preserving traditional games through digital initiatives. This study aims to identify and analyze digital strategies used by these pioneers to maintain the relevance of traditional games among younger generations. A qualitative research methodology with a case study approach was employed, involving field observations and interviews with key community pioneers across 14 districts (Kemantren) in Yogyakarta. The findings indicate that digital documentation, such as video tutorials and online content, is an effective strategy for preserving traditional games by making them accessible to a broader audience. Social media platforms, including YouTube, Facebook, and Instagram, are crucial in promoting traditional games and engaging younger generations. Additionally, community-led initiatives such as competitions, integrating traditional games into educational curricula, and training workshops have successfully revived interest in these games while fostering cultural awareness. The conclusion highlights that a combination of digital innovation and community engagement is vital for sustaining traditional games in the modern era. This study recommends further exploration of interactive digital technologies, such as augmented reality, to enhance the preservation and promotion of traditional games on a larger scale. The findings offer valuable insights for policymakers, educators, and cultural organizations in developing sustainable strategies to protect intangible cultural heritage in the digital age.